Development of Chemo-Selective Gas Sensors Based on Molecularly Imprinted Polymer-Quartz Crystal Microbalance for Detection of Bioactive Compounds in Curcuma longa - Hardoyono, Fajar (Universitas Gadjah Mada, 2025)
Turmeric contains bioactive compounds that are efficacious for human health. A breakthrough of simpler and lower-cost identification techniques is needed to utilize it. This paper aims to investigate the development of chemo-selective gas sensors for identifying α-curcumene, ar-turmerone, curlone, and β-sesquiphellandrene. Four chemo-selective sensors were created using quartz crystal microbalance (QCM) sensors coated with molecularly imprinted polymers to identify each of those compounds. The polymers were prepared using polyacrylic acid, hydrochloric acid, and pure target compounds (α-curcumene, ar-turmerone, curlone, and β-sesquiphellandrene). The turmeric odor from 10 different samples was exposed to QCM sensors. The changing frequency of QCM sensors due to the mass loading of target compounds on the surface of QCM sensors was recorded to analyze the performance of QCM sensors. The result of the principal component analysis showed that the QCM sensors performed well and could distinguish the turmeric samples at five combinations of the compounds. The turmeric sample classification using backpropagation neural networks reached high accuracies, with 97.04% in training and 98.73% in testing datasets. These findings indicate that the employment of sensory analysis using QCM sensors has the prospect of being a complementary technique for identifying bioactive compounds.